A Case Study of Ras Lanuf Oil Company Environmental Performance: Drivers and Measures - Dr. Embaraka Salem Hassan (مجلة جامعة سرت للعلوم الانسانية, 2023)
The purpose of this study is to shed light on the reality of the experience of measuring environmental performance as experienced by one Libyan oil and gas company. The aim of the exploratory case study is to extend prior empirical research by investigating possible drivers of the adoption of ISO 14001 EMS and measures of environmental performance amongst managers in RASCO. The exploratory single case study methodology was adopted since a case study provides a deeper understanding of the nature of management practice, especially when the issues under investigation have not yet been studied. To achieve this, method of data collection was conducted, namely, questionnaire,. Qualitative methods of data analysis, namely, descriptive analysis was adopted. The study findings revealed that environmental performance measurement at RASCO is still in its infancy and has obvious teething problems, such as setting indicators for measuring environmental performance since it difficult to quantify. It appears that the process of measuring environmental performance is still in the development stage since there is insufficient information about EPIs due to ISO 14031 EMS unknown in RASCO. The study found that the most important drivers to adopt ISO 14001 EMS in RASCO are to follow international oil and gas sector trends, to enhance RASCO‘s image, and to improve its environmental performance.